From Uyghur Muslims in China to the Uyghur Diaspora in Southeast Asia: A Political Reflection - Sahrasad, Herdi; Al Chaidar, Al Chaidar; Tabrani, Dedy; Hasan, Pipip A. Rifai (Jurnal Theologia, 2023)
This article discusses the problems of the Uyghur Muslims in Xinjiang, People's Republic of China, who have experienced mistreatment and violence from the communist regimes of Mao Zedong, Deng Xiaoping, Zhu Rongji, and Xi Jinping. Despite facing this treatment, the Uyghur Muslim minority has received criticism and negative labels for their resistance. The world community has also shown little attention to the Uyghur issue. This article aims to reveal the dynamics among Uyghur Muslims as they shift from nationalistic interests to their participation in acts of terrorism. This article uses a descriptive-analytical qualitative method based on data obtained from interviews, documents and literature studies. This article also explores the novelty of this topic by discussing the impact and implications of Uyghur Muslim involvement in global jihadist groups. For example, this article shows that thousands of Uyghur Muslims have become diasporas in other countries (Turkey, Afghanistan, Tajikistan, Middle East, Southeast Asia, etc.) seeking solutions to their problems, while being in a difficult and disadvantageous position . This article also explores the magnitude and extent of the activities and presence of Uyghur Muslims in Indonesia, such as in Aceh, Jakarta and Papua.